The Role of the Teacher as A Prototype of Students' Language Policy in Elementary School - Afidah, Nuri Novianti; Syihabuddin, Syihabuddin; Sauri, Sofyan; Hidayat, Mupid (Universitas Pendidikan Indonesia, 2025)
In today's world, the development of digital technology and social media has had a major impact on communication patterns, including the use of language. The language used in digital interactions often pays little attention to politeness norms. Seeing this problem, this study aims to develop politeness in language and communication, especially for students in elementary schools. This research uses a descriptive qualitative method with a phenomenological design through interview techniques with twenty students at the Az-Zahra Character Elementary School. Then get the results in the form of facts of violations of politeness in schools, this can be seen from every utterance or sentence and interaction between teachers and students or students with students that are expressed while in the school environment. Therefore, it is hoped that teachers can become prototypes of politeness in schools as a shaper of national character. This can be done by integrating positive politeness values in learning at school so that it is more optimal and of course useful in building harmonious relationships or establishing closeness between teachers and students which is where the teacher as a motivator and gives attention to students, or students with students for example, being able to cooperate in academic activities and be active in study group.